Influência da modalidade de enxertia e interação entre enxertos e porta-enxertos em mudas de Theobroma cacao L. submetidas a um ciclo de défice hídrico - Marinato, Claudio Sergio (2006)
The cocoa tree (Theobroma cacao L.) is comercially cultivated in large scale (great quantities). Nowadays, a production breakdown, caused by a prague named witches’ broom, came up with new challenges to the farmers. An option of strategy used to face it is the substitution of vulneable plants for more resistant genotypes. A good way to proceed this process is the use fo grafting techniques to accelerate the substitution of the tree pantry or to the speed uo the production of the trees. This method is also used to obtain plants with the desirable characteristics, more tolerant to dry weather periods and greater productivety. However, the success of grafting can be influenced by many factors, including the interaction between the graft and the rootstock, which can be influenced by both genotypes. The main goal was evaluating the level of resistance of the T. cacao grafts, applying two methods of precocious grafting, and the physiological characteristics of grafted trees when submitted to few quantities of water. The experience was conducted in green houses with controlled temperature and relative humidity of air. There have been used vegetable material the genotypes ESFIP 02, TSH 1188, CCN 51 and ‘Common Cocoa’. There have been tests of hipocotiledonar grafting by wrip grafting and soft wood. Taxes of survival and characteristics of the vegetative growth were analised. The experience was installed in delineation of randomized blocks with four repetitions in factorial arrangement 2x5, based on two two grafting methodsand four rootstocksadded to a frank foot. The percentage of survival was not influenced by the grafting methods. In the precociuos grafting the rootstock genotype influenced, meaningfully, the survival of genotypes TSH 1188 grafts. The ESFIP 02 genotupes, the grafting method of soft wood provided greater growth than the wrip grafting method. On the other hand, the hidric deficit reduced the quantities of height, leaf area, the stem dry mass and the leaves dry mass. The dry mass from the roots was higher in the stressed trees. The stress decreased the levels of leaf nitrogen; the levels of phosphorus and potassium increased, though. The hidric deficit influenced the levels of chlorophill, its fkuorescence, the gas exchanges and the leaves hidric potential negativelly. O rootstock genotype influenced meaningfully the tolerance to hidric deficit and in the analised topics. The ESFIP 02 genotype, when used as rootstock permitted, generally higher levels of vegetative growth, dry mass accumultated, the leaves hidric potencial, chlorophill fluorescence and liquid photosynthesis